Advancing understanding of the formation and stability of soil organic matter in a changing environment - Lavallee, Jocelyn M., author; Conant, Rich T., advisor; Paul, Eldor A., advisor; Cotrufo, M. Francesca, committee member; Borch, Thomas, committee member; Kelly, Eugene F., committee member (Colorado State University. Libraries, 2015)
Soil is one of our most precious natural resources. It plays a key role in maintaining soil fertility and water quality, and represents a major reservoir in both the global carbon (C) and nitrogen (N) cycles. Soils contain more C and reactive N than the atmosphere and all vegetation combined, the majority of which is found in soil organic matter (SOM). Despite its considerable significance, little is known about the factors that control the formation of SOM, and its stability in the environment. Key questions pertain to whether environmental changes will increase the production of CO₂ during SOM formation and decomposition, forming a large positive feedback to climate change. Answering those questions required a better understanding of how various mechanisms that confer SOM stability are affected by environmental change. My dissertation research aimed to address some of these key questions, and to advance our overall understanding of SOM formation, SOM stability, and the response of stable SOM to changes in the environment. First, I conducted two soil incubation experiments using isotopically labeled (¹³C and ¹⁵N) plant material, which allowed me to track the incorporation of plant-derived C and N into SOM, and efflux of plant-derived C in CO₂. In one soil incubation, I tested the effects of plant litter quality and on the rate and efficiency of SOM formation (a measure of the amount of SOM formed versus the amount of CO₂ lost in the process) by comparing SOM formation from leaves versus roots. I found that plant litter chemistry (C/N ratio) was a reliable predictor of SOM formation after the initial stage of decomposition, with low C/N ratios resulting in more SOM formation and higher formation efficiencies overall. In the second soil incubation, I tested the effect of warming on the rate and efficiency of SOM formation, as well as the rate of destabilization of stable SOM. I found that warming generally led to lower formation efficiencies, causing greater CO₂ production per unit of SOM formed. Warming also led to higher rates of destabilization of stable SOM throughout the experiment. Next, I aimed to investigate the effect of warming on SOM in the field, using soils from two multi-factor climate change experiments. Results from that study suggested that while warming increased the rate of turnover of SOM in some cases, any resulting losses of SOM were offset by increased inputs of SOM, so that total SOM stocks were unchanged. Last, I investigated the persistence of pyrogenic SOM, which is thermally transformed by fire, in the face of land use change at three agricultural sites across the US. I found that pyrogenic SOM was present in all three soils, and had persisted to a greater extent than other SOM with land use change. Many studies of SOM dynamics do not account for pyrogenic SOM, and the results of my work suggest that this lack of accounting can preclude us from fully understanding the mechanisms behind SOM stability. Overall, my work advances our understanding of stable SOM in terms of how it is formed, and whether it will persist in the face of environmental change. Changes in plant litter quality and temperature may lead to changes fluxes of CO₂ to the atmosphere during SOM formation, and while some SOM (pyrogenic SOM) is highly stable in the environment, other SOM is susceptible to loss with warming and land use change. However, in the case of warming, increased plant inputs may offset increased rates of SOM decomposition.
Keywords: land use change; pyrogenic carbon; soil organic matter; litter quality; climate change; soil carbon